Identification and characterization of kink motifs in 1-palmitoyl-2-oleoyl- phosphatidylcholines: a molecular mechanics study. - Li, S (1994)
As a cis carbon-carbon double bond (delta) is introduced into the middle of an isolated all-trans hydrocarbon chain, it can be shown by molecular graphics that this delta-bond makes a bend of 130 degrees in the chain axis, thus producing a boomerang-like conformation. Such a bent structure, indeed, has been detected experimentally for oleic acid by x-ray crystallography (Abrahamson and Ryderstedt-Nahringbaur, 1962). Membrane diacyl phospholipids are largely mixed-chain lipids containing a saturated sn-1 acyl chain and an unsaturated sn-2 acyl chain. 1-Palmitoyl-2-oleoyl-phosphatidylcholine (POPC), the most abundant phospholipid in animal cell membranes, is a typical example in which the sn-2 acyl chain is the acyl chain of an oleic acid. However, this sn-2 acyl chain of POPC is unlikely to adopt a boomerang-like configuration in the gel-state lipid bilayer due to the steric hindrance imposed by neighboring chains. Instead, it has been suggested that the oleate chain in POPC is kinked in the shape of a crankshaft in the gel-state bilayer (Huang, 1977; Lagaly et al., 1977), because POPC with such a kinked sn-2 acyl chain, which is denoted here as the secondary structural element or motif, can pack efficiently against other neighboring phospholipids. In this communication, 16 different types of secondary structural elements or motifs are derived for POPC at T < Tm based on a single protocol guided by two-dimensional steric contour maps and computer-based molecular graphics. After subjecting these derived molecular species to energy minimization using the molecular mechanics method, the number of the secondary structural motifs is reduced to 13 as a result of conformational degeneracy. The structure and steric energy of each of the energy-minimized lipid rotomers are presented in this communication. Furthermore, these rotomers packed in small clusters are also simulated to mimic the lipid bilayer structure of 1-palmitoyl-2-oleoyl-phosphatidylcholines at T < Tm.